Sedimentary architecture of the Brown Bank Formation (Dutch sector of the North Sea) reveals consecutive shallow marine depositional phases during the MIS 5-4 transition - Irene Waajen-Labee; Ruth Plets; Víctor Cartelle; Marieke Cuperus; Timme Donders; Sytze van Heteren; Thomas Mestdagh; Friederike Wagner-Cremer; Jakob Wallinga; Frank Wesselingh; Freek Busschers (Quaternary Science Reviews, 2025)

Harnessing methods, data analysis, and near-real-time wastewater monitoring for enhanced public health response using high throughput sequencing - Padmini Ramachandran; Tunc Kayikcioglu; Tamara Walsky; Kathryn Judy; Jasmine Amirzadegan; Candace Hope Bias; Bereket Tesfaldet; Maria Balkey; Dietrich EppSchmidt; Hugh Rand; James Pettengill; Sandra Tallent; et al. (Environmental Research, 2025)

Late MIS5a in the southern North Sea: new chronostratigraphic insights from the Brown Bank Formation - Irene M. Waajen; Freek S. Busschers; Timme H. Donders; Sytze Van Heteren; Ruth Plets; Jakob Wallinga; Rick Hennekam; Gert‐Jan Reichart; Tim Kinnaird; Friederike Wagner‐Cremer (Journal of Quaternary Science, 2024)
The Brown Bank Formation (BB Fm) is a clay‐rich sedimentary unit that is distributed over a large area in the southern North Sea. It is easily recognisable in 2D acoustic reflection profiles, forming sets of subparallel high‐amplitude reflections. Previous studies have provided only fragmentary information on the facies, and a variety of interpretations on the depositional environment and age of the BB Fm. In this study we combine high‐resolution 2D acoustic reflection profiles and multiproxy sedimentological, geochemical and geochronological analyses of three vibrocores, to provide a detailed description and a new age assessment for the BB Fm at its type locality, adjacent to the Brown Bank ridge. At the study site, the BB Fm shows morphologically well‐preserved submarine sand dunes, deposited in a high‐energy shelf setting, overlain by organic‐rich silty clays that were deposited under lower‐energy conditions in an increasingly compartmentalised marginal marine environment. Elevated terrestrial organic input shows that the Rhine–Meuse delta was situated relatively close‐by. Luminescence ages indicate that the sediments of the BB Fm in our cores were deposited during the Weichselian Odderade interstadial (MIS5a, ca. 80 ka) and earliest parts of the Early Pleniglacial (MIS4, ca. 70 ka), which is later than previously reported in the literature.